Rwanda: Impacts of the Ukraine and global crises on poverty and food security - Diao, Xinshen; Dorosh, Paul A.; Thurlow, James; Spielman, David J.; Smart, Jenny; Benimana, Gilberthe Uwera; Mugabo, Serge; Rosenbach, Gracie (International Food Policy Research Institute, 2022)
Global food, fuel, and fertilizer prices have risen rapidly in recent months, driven in large part by the fallout from the ongoing war in Ukraine and the sanctions imposed on Russia. Other factors have contributed to the crisis, such as export bans and continued supply chain disruptions from the COVID-19 pandemic. For example, between June 2021 and April 2022, the global prices of palm oil and wheat increased by 56 and 100 percent in real terms, respectively. At the same time, the price of fertilizer doubled, while crude oil and natural gas prices have also risen substantially. However, wide variation also exists across commodities, with real maize prices increasing by only 11 percent, and rice prices declining by 13 percent (Figure 1).